Nursing Student’s Perception of Satisfaction and Self-Confidence with Skill Laboratory Practice - Sah, Bimala Kumari; Gachhadar, Rashmi (Journal of Nursing Education of Nepal, 2023)
Introduction: Nursing students go through series of theory and practical sessions before accomplishing the nursing course. It is necessary for the students to gain master in basic procedures prior to practicing on real patients. Therefore, students best learn to perform nursing procedures in skill laboratories through demonstrations and simulations. The current study aims to assess the nursing students’ perception on satisfaction and self-confidence towards skill laboratory practice.Methods: A descriptive cross sectional research design with total enumeration technique was used. Self- administered technique was used to collect data from 78 respondents. The data was analyzed  in SPSS software version 20 using descriptive analysis.Results: The mean age of the students was 20.35±1.43. Out of 78 students, half (51.3%) were involved in fundamental laboratory, while, 48.7% were involved in Midwifery laboratory practice. More than half of the students (56.4%) were satisfied with the skill laboratory practice, and half of the students (50%) had high self-confidence to practice in actual clinical setting after skill laboratory practice.Conclusion: More than half of the students were satisfied and half of them had high self-confidence, and there is still need to put more efforts towards improving the practice in order to exceed the current quantity as well as the quality of practice.
Keywords: Nursing students; Practice Satisfaction; self-confidence; skill laboratory